Innate talent is adaptable - comment on Baker & Wattie - Michael Romann (Bern Open Publishing, 2019)
An the recent article by Baker and Wattie (2018), they provided an update on the widely cited review of "Innate Talent" by Howe, Davidson and Sloboda (1998). The article summarizes that the defined criteria for "Innate Talent" are still valid, standing the test of time. However, new findings in epigenetics should be considered. The epigenome interacts with environmental factors, such as physical exercise, contributing to phenotypical and performance differences of the same gene. In this context, researchers in sport science face the task of defining ethical standards that are accepted by society. From an epigenetic perspective, one should refrain from thinking that genetics have a fixed performance outcome, since the epigenome is adaptable. Instead, research and practice should consider how created environments support athlete development.